Study on the serum and gene expression profile of cytokines and the role of cytokine gene polymorphism on susceptibility to hepatitis c infection in Malay male drug abusers - Noh, Che Ismail Che (2023)
Chronic hepatitis C virus (HCV) infection is one of the major causes of liver cirrhosis and carcinoma. The underlying pathophysiology may be due to variations in immunomodulatory cytokine activities rather than the direct action of the virus itself. The objectives of this study were to investigate the serum levels and gene expression of cytokines and the possible association of cytokine gene polymorphism on susceptibility to hepatitis C infection in Malay Male drug abusers. The selection of the subjects provides novel knowledge in understanding the high occurrence of chronic HCV among drug abusers, a vulnerable and often neglected group of patients. Interleukin-10 (IL-10) rs1800896 and rs1800871, interleukin 6 (IL-6) rs1800795, tumour necrosis factor (TNF)-α rs1800629 and tumour growth factor (TGF)-β1 rs1800471 have been selected for the investigations representing anti and proinflammatory cytokines. A total of 162 subjects were enrolled from various health clinics in Kelantan, Malaysia, and divided into two groups: 76 patients with chronic HCV infection (HP) and 86 control group (HS). The gene polymorphisms were detected through multiplex polymerase chain reaction (PCR), gene expressions by real-time reverse transcriptase polymerase chain reaction (RT-PCR), and the serum cytokine levels were measured by immunoassay. There were significant differences in the frequencies of genotype for IL-10 rs1800896 (p = 0.0422), IL-10 rs1800871 (p = 0.0498), and at the allelic level for IL-10 rs1800896 A versus G allele (p = 0.0142), TGF-β1 rs1800471 (p = 0.0051) and at the allelic level for TGF-β1 rs1800471 G versus C allele (p = 0.0082) in the HP group and the control group. The study discovered a significant difference in gene expression for TNF-α (p = 0.0328) and in the mean serum levels of IL-6, and TGF-β1 in the HP group compared to the HS group (p = 0.0180 and p = 0.0005, respectively). These findings suggest significant associations between gene polymorphisms for IL-10 rs1800896, IL-10 rs1800871, TGF-β1 rs1800471 and susceptibility to HCV infection among Malay male patients with chronic HCV infection. Gene expression of TNF-α and serum expression of IL-10, IL- 6 and TGF-β1 shows a significant association with chronic HCV infection. This study provides a novel insight into the role of cytokines and genetic variation on susceptibility to chronic HCV infection among Malay male drug abusers, discovering potential genetic and serum biomarkers for the disease, and eventually towards precision medicine for chronic HCV infection, particularly for drug abusers.